Outcome of Patients With IDH-Mutated AML Following Allogeneic Stem Cell Transplantation—A Retrospective Analysis on Behalf of the German Registry for Hematopoietic Stem Cell Transplantation and Cell Therapy, DRST - Schroeder, Thomas; Flossdorf, Sarah; Schuh, Claudia; Pabst, Caroline; Stadler, Michael; Schetelig, Johannes; Wehr, Claudia; Stelljes, Matthias; Sala, Elisa; Burchert, Andreas; Winkler, Julia; Reinhardt, H. Christian; et al. (Transplantation and Cellular Therapy, 2025)
Mutations in isocitrate dehydrogenase 1 and 2 genes (IDH1 and IDH2) are found in 15% to 20% of patients with acute myeloid leukemia (AML). IDH inhibitors have been introduced as targeted treatment and are currently under investigation as maintenance therapy after allogeneic transplantation (allo-SCT). Since reports about the outcome of IDH1- and IDH2-mutated (IDHmut) AML after allo-SCT are limited, we retrospectively analyzed 356 IDH-mutated AML patients (IDH1 40%, IDH2 60%). Ten patients (4%) had received an IDH inhibitor prior transplantation, but none had received maintenance with IDH inhibitors. After a median follow-up of 24 months 3-year probabilities of overall (OS) and event-free (EFS) survival, relapse and nonrelapse mortality (NRM) for the entire cohort were 73%, 60%, 27% and 13% respectively. While 3-year OS (78% versus 70%), EFS (56% versus 63%) and NRM (10% versus 14%) rates were similar for IDH1mut and IDH2mut patients, relapse incidence was numerically higher in IDH1mut patients (34% versus 24%) and landmark analysis suggested a continuous rise of relapse incidence preferentially in IDH1mut AML also beyond the first year. Concordantly, IDH2 mutation was associated with superior EFS and by trend with lower relapse incidence. The strongest risk factor for adverse outcomes, however, was AML not in CR. This analysis provides benchmarks for interpretation of results emerging from post-transplant maintenance trials in IDHmut AML and suggest that maintenance strategies may further optimize the promising outcome in this molecularly defined subgroup by reducing relapse risk, especially for patients whose AML is not in remission at time of alloHCT.
CRIS-Team Scopus Importer:2025-04-04
Keywords: Allogeneic transplantation; AML; IDH mutation; Maintenance; Relapse